Mechanical characteristics and FEA-based non-uniform infill density approaches for Fused Deposition Modelling (FDM)-printed components: A literature review - Mhd. Fahri Meihanda Putra; Syahril Syahril; Delima Yanti Sari (Researcher and Lecturer Society, 2026)
Fused Deposition Modelling (FDM) is one of the most widely used additive manufacturing (AM) technologies for producing functional polymer components. However, commercially available slicing software generally applies a uniform infill density throughout the entire component without considering the actual stress distribution, resulting in excessive material usage in low-stress regions and unnecessary increases in component weight. This literature review synthesizes current knowledge on the mechanical characteristics of FDM-printed components and evaluates Finite Element Analysis (FEA)-based non-uniform infill density approaches as a promising strategy for structural optimization. The reviewed literature covers the effects of anisotropic behaviour, internal voids, infill density, infill pattern, and the integration of FEA with topology optimization techniques for FDM components. The findings indicate that the layer-by-layer deposition process produces pronounced mechanical anisotropy and introduces internal voids that influence structural performance. The relationship between infill density and mechanical strength is positive but nonlinear, whereas different infill patterns at the same density can produce variations of up to 82% in flexural strength. Although FEA provides reliable estimates of stress distribution, prediction errors of approximately 8.67–12% remain because conventional simulations assume homogeneous and isotropic materials that do not accurately represent the actual characteristics of FDM-printed components. Furthermore, FEA-based multi-zone non-uniform infill density strategies have been reported to increase peak load by up to 49% and bending stiffness by up to 46% compared with conventional uniform-density configurations. Overall, this review demonstrates that FEA-based non-uniform infill density is a promising design optimization strategy for functional FDM-printed components by improving structural performance while reducing unnecessary material usage. Future research should focus on density transition design and experimental validation to improve the reliability and practical implementation of this approach.